2015
DOI: 10.1016/j.eats.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Arthroscopically Assisted Transtrochanteric Drilling for Femoral Head Chondral Defects

Abstract: Microfracture is a marrow-stimulation technique in which damaged cartilage is drilled or punched, perforating the subchondral bone and generating a blood clot within the defect that matures into fibrocartilage. Microfracture for the treatment of small cartilage defects of the hip has shown good results. Arthroscopic procedures are less invasive than open procedures and have a reduced incidence of complications such as infection or avascular necrosis of the femoral head. Furthermore, arthroscopic procedures all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…28 Likewise, we believe that size of the OCD is of utmost importance to indicate an arthroscopic-assisted procedure, as it does not seem reasonable to treat a defect greater than 2 cm with this technique. 11 Therefore, we suggest that greater OCDs should be treated with reattachment of the fragment through surgical hip dislocation and internal fixation. Lamplot et al 29 have reported predictable x-ray healing and significant clinical improvement following open reduction and internal fixation at mean follow-up of 4.6 years in a series of 7 patients with osteochondritis dissecans with underlying Perthes disease.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…28 Likewise, we believe that size of the OCD is of utmost importance to indicate an arthroscopic-assisted procedure, as it does not seem reasonable to treat a defect greater than 2 cm with this technique. 11 Therefore, we suggest that greater OCDs should be treated with reattachment of the fragment through surgical hip dislocation and internal fixation. Lamplot et al 29 have reported predictable x-ray healing and significant clinical improvement following open reduction and internal fixation at mean follow-up of 4.6 years in a series of 7 patients with osteochondritis dissecans with underlying Perthes disease.…”
Section: Discussionmentioning
confidence: 98%
“…4,[22][23][24][25] Lately, due to patients reluctance to undergo a major surgery, there has been a trend towards developing arthroscopic alternatives, including transtrochanteric drilling and even arthroscopic retrograde osteochondral autologous transplantation. 11,26,27 In this scenario, we intended to report the outcomes of an arthroscopically assisted, percutaneous retrograde drilling of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations